Hubungan Model Non Directive Teaching dengan Motivasi Belajar Bahasa Arab Siswa SMK Muhammadiyah Prambanan - Nurlaila Nurlaila (LP4MK STKIP PGRI Lubuklinggau, 2019)
This study aims to determine the relationship of the application of the nondirective teaching model to the Arabic learning motivation of SMK Muhammadiyah Prambanan students. This research uses quantitative methods with correlation design. The research instrument used was interviews, observation, documentation, and questionnaires distributed to 104 students from a total population of 245 class XI students, which then tested the validity, reliability, normality, and linearity. To find out the significance of the relationship and the effect of the nondirective teaching model with learning motivation, a correlation test, and a regression test was performed. From the calculation using the product-moment correlation coefficient formula, it is known that there is a positive and very significant relationship between the application of the nondirective teaching model with the motivation to learn Arabic class XI students at SMK Muhmmadiyah Prambanan by rxy 0.428 and the effective contribution of the application of the nondirective teaching model to language learning motivation Arabic is only 18.3% (R square 0.183) while 71.3% of students' Arabic learning motivation is influenced by other factors. Therefore, to improve the quality of learning, the application of the nondirective teaching model needs to be packaged with a variety of supportive learning methods, both for the nondirective counseling process and as well as the desired learning objectives. This is because student motivation is a variable that is influenced by various factors.